Characterization of platelet factor 4 amino acids that bind pathogenic antibodies in heparin‐induced thrombocytopenia. (8th February 2019) - Huynh, Angela; Arnold, Donald M.; Kelton, John G.; Smith, James W.; Horsewood, Peter; Clare, Rumi; Guarné, Alba; Nazy, Ishac
Abstract : Essentials Many patients produce antibodies but few lead to heparin‐induced thrombocytopenia (HIT). Pathogenic epitopes are difficult to identify as HIT antibodies are polyclonal and polyspecific. KKO binding to platelet factor 4 (PF4) depends on 13 amino acids, three of which are newly observed. Five amino acids in PF4 can help distinguish pathogenic from non‐pathogenic antibodies. Summary: Background: Heparin‐induced thrombocytopenia (HIT) is an adverse drug reaction that results in thrombocytopenia and, in some patients, thrombotic complications. HIT is mediated by antibodies that bind to complexes of platelet factor 4 (PF4) and heparin. The antigenic epitopes of these anti‐PF4/heparin antibodies have not yet been precisely defined, because of the polyspecific immune response that characterizes HIT. Objectives: To identify PF4 amino acids essential for binding pathogenic HIT antibodies. Methods: Alanine scanning mutagenesis was utilized to produce 70 single point mutations of PF4. Each PF4 mutant was used in an enzyme immunoassay (EIA) to test their capacity to bind a platelet‐activating murine monoclonal anti‐PF4/heparin antibody (KKO) and HIT patient sera ( n  = 9). Results and Conclusions: We identified 13 amino acids that were essential for binding KKO because they directly affected either the binding site or the antigenic conformation of PF4. We also identified 10 amino acids that were required for the binding of HIT patient sera and five of these amino acids were required for binding both KKO and the HIT patient sera. The 10 amino acids required for binding HIT sera were further tested to differentiate pathogenic HIT antibodies (platelet activating, n  = 45) and non‐pathogenic antibodies (EIA‐positive but not platelet activating, n  = 28). We identified five mutations of PF4 that were recognized to be essential for binding pathogenic HIT antibodies. Using alanine scanning mutagenesis, we characterized possible binding sites of pathogenic HIT antibodies on PF4.